The effect of circuit training using tools and without tools on archery score results - Yudh, P. K. (Ibero-American Journal of Exercise and Sports Psychology, 2024)
The purpose of this study was to compare and analyse the effect of circuit training using tools and without tools on the results of archery scores at distances of 50, 40, and 30 meters archery athletes. This study uses an experimental method with a two group pre test and post test design, a population of 38 South Sumatra archers, sampling using purposive sampling so that 32 archers of the national round are obtained, the analysis technique uses paired sample t and Independent Sample T-test at the significance level a (0.05). The results of this study: there is a significant difference between circuit training using tools and without tools on the results of archery scores at distances of 50, 40, and 30 metres with a sig value of 0.021 <0.05. The conclusion of this study shows that: there is a significant difference between circuit training using tools and without tools on the results of archery scores at distances of 50, 40, and 30 metres.